PERANCANGAN MOTION COMIC SEBAGAI MEDIA EDUKASI PENCEGAHAN BULLYING TERHADAP SISWA SEKOLAH - Muhammad Wahyu Illahi; Henny Lukitasari, Evelyne; Khoirul Anwar, Ahmad (Universitas Sahid Surakarta, 2024)
The use of digital media makes it very easy to find various kinds of information on the internet. The use of the internet can make it easier for people in their daily activities, especially students. However, this convenience makes many students misuse the internet. Many students enjoy watching entertainment content with violent themes. This causes a lot of bullying in the school. Bullying that occurs in the school environment can cause victims to suffer from mental disorders. This can affect the future of students and make it difficult for students to grow both in terms of character and knowledge. Therefore, education is needed to prevent bullying. Motion comics are used as educational media to prevent bullying. The media is chosen because it is able to convey information clearly with a more interesting impression so that it can be well received by the audience. The design method used in this final assignment is the Antelope studio design method. This design method is divided into 5 stages, namely: development, pre-production, production, post-production, and distribution. The design of this motion comic final assignment is intended as educational, as well as useful entertainment content.